Divergent definitions in the visibility strategy of the LGTB movement in Cordova - Iosa, Tomás (2011)
This article explores visibility as a problem, an objective and a strategy of LGTB activism. Focusing on the recent appropriation of the Pride March as a political practice on the part of one sector of the LGTB Cordova movement, the author examines how activists dispute legitimate modes of articulating a visibility strategy. Marked by the risk of commercialization and an emptying of political content, the march nevertheless constitutes a stage for new and opposing definitions of the citizen status of sexual-gender diversity. Based on field observations and interviews with activists, the author interrogates how the trajectory in militancy, the sexualgender subjectivities at play, differential access to resources and the relatively radical character of their platforms constitute determining factors in the definition of the visibility strategy in ‘festive’ or ‘combative’ terms.